Barriers and facilitators to digital health collaboration between academia and industry: a cross-cultural analysis - Chelsea Liu, BA; Shuai Shao, MSc; Janet Prvu Bettger, ScD; Chang Liu, PhD; Lijing Yan, PhD (Elsevier, 2019)
Background: In a landscape of rising chronic disease burden in middle-income and high-income countries, digital health is seen as a promising solution to improving population health. Importantly, the development and uptake of digital health technologies require multisectoral efforts from academia and industry. However, few have explored the factors that help or hinder the success of these collaborations. Our study aims to identify the themes, barriers, and facilitators associated with industry-academia collaborations in digital health in middle-income and high-income countries. Methods: Trained researchers conducted semi-structured interviews with 23 stakeholders who are active in industry (n=11), academia (n=11), or both (n=1) using prespecified interview guides. Stakeholders were based in World-Bank-defined middle-income countries (China, India; n=15) or high-income countries (USA, Australia, Singapore; n=8). Interviews were conducted in the stakeholder's language of choice (Chinese, n=12; English, n=11). Qualitative interview questions elicited discussions about stakeholders' past experience with academia-industry collaboration, challenges they faced, and factors that facilitated the process. Interviews were audiotaped, transcribed verbatim, and analysed using inductive content analysis. A codebook was developed by the research team over five iterations and used by two bilingual coders to thematically code the data. Findings: Four central themes emerged from the discussions: stakeholder role in collaboration, communication between partners, goals or expectations, and individual priorities. Stakeholders in both academia and industry identified several facilitating factors for successful collaborations: the adoption of complementary roles; authentic communication between partners; and clearly outlined goals or expectations before the collaboration begins. Misaligned goals or expectations, particularly differences in timeline and difficulties balancing business outcomes versus scientific evidence, were identified as the primary barriers. Stakeholders in high-income countries reported inauthentic communication as a significant barrier to collaboration, whereas those in middle-income countries did not. Interpretation: This study highlights the need for increased planning and communication prior to and throughout collaborations between academia and industry in the field of digital health. Outlining each party's goals and expectations about timelines, assigning complementary roles, and communication about priorities will facilitate fruitful collaborations in the future. Furthermore, best practices for communication styles may depend on the cultural setting and, thus, should be adopted accordingly. Funding: None.